THE COMMITMENT TO ISLAMIC WORK ETHICS AMONG ISLAMIC BANKING EMPLOYEES IN ACEH - Ibrahim, Azharsyah; Kamri, Nor ’Azzah (Jurnal Syariah, 2017)
Ethics play an important role in producing ethical staffs for managing an organization. Ethical staffs perform their duties ethically and offer the best services to the customers. Islamic banking institutions, as Shariah compliant financial institutions, should encourage their employees to implement Islamic work ethics (IWE) to enhance their performance. This article aims to examine the level of IWE commitment among employees of Islamic banks in Aceh. It specifically compares the employee’s commitment level on IWE between three categories of Islamic banking in Aceh, namely, the Islamic Commercial Bank (ICB), the Islamic Business Unit (IBU), and the Islamic Rural Bank (IRB). The study employed a quantitative approach in collecting data. The questionnaire surveys were distributed to 268 employees in seven Islamic banks. Of that number, only 208 were usable. The results of the findings reveal that employees of the selected Islamic banks in Aceh have very high commitment to implementing IWE in their daily routines. An analysis of the banking categories shows that the employees who work within the IBU have the highest commitment in practicing IWE in their daily jobs, and, statistically, differ from those who work in the other two categories.